(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The objective of the research is to determine the perception of higher-level students regarding entrepreneurship, through a survey prepared by experts, which allows knowing their points of view about their creativity, business vision and the possibility of implementing their business idea. The method is of quantitative approach, since the data are quantifiable and allow the objectivity of the results when addressing a certain sample of the population; Its scope is exploratory, because it investigates problems or topics on which there is little documentation, and it is descriptive, because it details the profile of the participants, collecting all possible data that contribute to the research. Finally, it is transactional, since the field data collection was carried out on a single occasion and in a certain place. It can be concluded that university students have a favorable perception regarding entrepreneurship, however, some manifest fear of being entrepreneurs due to the risk of failure, specifically because they do not have enough skills or lack of inspiration that motivates them to get out of your status quo. There is a very fine line between men and women in terms of initiative when deciding to undertake, the age of greatest interest is 18 to 22 years and marital status is single.